2014
DOI: 10.1080/1536383x.2014.974090
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Preparation Process on Morphology and Conductivity of Carbon Black-Based Electrospun Nanofibers

Abstract: In this work, three different methods of preparation of polyacrylonitrille (PAN) with carbon black (CB) solutions further used in electrospinning for producing conductive fiber mats are discussed. CB is used as conductive filler. Content of CB in polymer matrix is varied, CB/PAN D 1/2, 1/1, and 3/2. The solution properties and obtained fiber morphology are analyzed. The effect of preparation on fiber morphology and conductivity is analyzed, as well as the effect of sonication on solution properties, morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In its turn, modification of whipping instability can improve fiber morphology and help to avoid formation of beads, as it was shown by us in Ref. [28].…”
Section: Introductionmentioning
confidence: 77%
“…In its turn, modification of whipping instability can improve fiber morphology and help to avoid formation of beads, as it was shown by us in Ref. [28].…”
Section: Introductionmentioning
confidence: 77%
“…The chain-like aggregation structure of CB particles forms a stronger conductive network than that of other carbon-based materials and, at the same time, the higher filler content leads to little combining with the polymer matrix. 74 CF has become an attractive shielding material due to its high specific strength and high conductivity. However, the absorption capability of CF is poor, which results in poor further attenuation of electromagnetic waves when used as a single medium.…”
Section: Electromagnetic Shielding Materialsmentioning
confidence: 99%
“…It has been over one decade that carbon black (CB) nanoparticle became one of the interesting materials to modify polymer nanofiber due to small particle size (high surface area), aggregation behavior, low cost and conductive property [20][21] Those properties make CB has usability as an adsorbent material [22]. Islam et al [23] reported that CB is the most effective adsorbent material than extruded activated carbon and granular activated carbon.…”
Section: Introductionmentioning
confidence: 99%